2007
DOI: 10.1177/112067210701700317
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Alterations in P27Kip1Knockout Mice

Abstract: The morphologic and morphometric results suggest that homozygous P27(Kip1) knock-out mice had hypertrophic, hyperplastic, and dystrophic ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Moreover, the migratory and differentiation capabilities of glial progenitors are perturbed during E13 to E19 in p27 KIP1 null mice, as there were significant increases in QKI-positive; BrdU-positive cells in the subventricular zone compared to wild-type controls [42]. In addition, reduction in MBP staining is observed in p27 KIP1 knockout mice in the optic nerve, consistent with the requirement for p27 KIP1 and PNS myelination [43]. We have previously showed that p27 KIP1 increases after the ectopic expression of QKI-6/7 in oligodendrocytes [8].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the migratory and differentiation capabilities of glial progenitors are perturbed during E13 to E19 in p27 KIP1 null mice, as there were significant increases in QKI-positive; BrdU-positive cells in the subventricular zone compared to wild-type controls [42]. In addition, reduction in MBP staining is observed in p27 KIP1 knockout mice in the optic nerve, consistent with the requirement for p27 KIP1 and PNS myelination [43]. We have previously showed that p27 KIP1 increases after the ectopic expression of QKI-6/7 in oligodendrocytes [8].…”
Section: Discussionmentioning
confidence: 94%
“…It is expressed in many adult glial populations including Schwann cells, cortical astrocytes, spinal cord astrocytes, oligodendrocytes, and retinal Müller glia [23-27]. In germline p27-deficient mice ( p27 -/- ), adult glia can display hallmarks of reactive gliosis [24-26,28]. In the wild-type retina, quiescent Müller glia normally do not express the intermediate filament glial fibrillary acidic protein (GFAP), but Müller glia in p27 -/- mice express high levels of GFAP and in some instances migrate into the subretinal space [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…47 ), in the murine retina p27 Kip1 is also expressed by precursor cells during late G2/early G1. 65 The expression of p27 Kip1 in the mouse retinal precursors may explain both the increase of RGC axons in the optic nerve 66 and the retinal dysplasia [67][68][69] observed in p27 Kip1¡/¡ mice. Nevertheless, the increase of RGC number in the retina of p27 Kip1¡/¡ mice that would explain this phenotype is not dramatic, 66 and seems to be compensated by apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…65 The expression of p27 Kip1 in the mouse retinal precursors may explain both the increase of RGC axons in the optic nerve 66 and the retinal dysplasia [67][68][69] observed in p27 Kip1¡/¡ mice. Nevertheless, the increase of RGC number in the retina of p27 Kip1¡/¡ mice that would explain this phenotype is not dramatic, 66 and seems to be compensated by apoptosis. 44,65 In this context, interfering RNA against p27 Kip1 has been shown to induce cell death in cultured cortical neurons.…”
Section: Discussionmentioning
confidence: 99%